Hydromagnesite sheets impregnated with cobalt–ferrite magnetic nanoparticles as heterogeneous catalytic system for the synthesis of imidazo[1, 2-a]pyridine scaffolds. Issue 38 (1st July 2021) - Geedkar, Deepika; Kumar, Ashok; Kumar, Kranti; Sharma, Pratibha
Abstract : Sustainable synthesis of imidazo[1, 2- a ]pyridine scaffolds assisted by hydromagnesite sheets impregnated with cobalt–ferrite (CoFe2 O4 -HMS) magnetic nanoparticles (MNPs). Abstract : This paper manifests an A 3 -coupling strategy assisted by novel hydromagnesite sheets impregnated with cobalt ferrite (CoFe2 O4 -HMS) magnetic nanoparticles (MNPs) as an environmentally benign nanocomposite to synthesize imidazo[1, 2- a ]pyridine scaffolds under ultrasonication. The synthesis of these biologically active derivatives was achieved through A 3 -coupling employing 2-aminopyridines derivatives, pertinent aryl aldehydes, and phenylacetylene in the presence of polyethylene glycol 400 (PEG 400) as a green solvent under aerobic conditions. Based on its high product yield (up to 94%) in a short reaction time, with a modest catalyst loading, excellent catalyst, and solvent recyclability without substantial loss of operation (up to five synthetic cycles), as demonstrated by the high ecological compatibility and sustainability factors, this strategy follows the principles of green chemistry. The synthesized nanocomposite was characterized via several spectroanalytical techniques, including PXRD, FE-SEM, HR-TEM, EDAX, ICP-AES, FT-IR, Raman spectroscopy, CO2 -TPD, TGA-DTA-DTG analyses, magnetic studies, and nitrogen porosimetry. Furthermore, the structures of synthesized compounds were confirmed based on FT-IR, 1 H NMR, 13 C NMR, mass spectroscopy, and elemental analysis data.